Impact of instruction based on movie and TV series clips on EFL learners’ pragmatic competence: Speech acts in focus - Omar, Fouad Rashid; Razı, Özge (Frontiers in Psychology, 2022)
This study attempts to investigate the role of movie and TV series clips in enhancing EFL learners’ pragmatic competence by utilizing an experimental design. The sample of the study was 42 students from the English language department at Cihan University-Duhok, Iraq. The experiment lasted one academic semester. The participants' English language proficiency, as determined by an IELTS test sample, was intermediate, and then they were randomly split into two groups, namely experimental and control. Before and after the treatment, a Written Discourse Completion Test (WDCT) served as a pre-and post-test given to the two groups to assess statistically significant differences between them. The experimental group received direct instruction on request and suggestion speech acts via the presentation of the carefully chosen movie and TV series clips. In contrast, the control group was exposed to a minimal amount of pragmatics through printed texts. The findings demonstrated that the experimental group outperformed the control group. More precisely, the findings revealed that movie and TV series clips had a significant influence on learners' production of requests and suggestions. Considering the above findings, the researchers propose EFL teachers apply movie and TV series clips to improve their students' pragmatic competence in class.